Evaluation of Potential in Wonderful Kola (Buchiolizia coreica) Seed Extract on Streptozotocin Induced Type 2 Diabetes in Male Wister Rats - Umaru, Isaac John; Onyinyechi, Nwachukwu Favour; Tansaba, Akafa Andes; Nanmar, Chakfa; Umaru, Kerenhappuch Isaac; Ugoeze, Egeonu Stephen; Galam, Nanyak Zingfa (Darul Yasin Al Sys, 2024)
Diabetes mellitus is referred to as a metabolic disorder in which there is high glucose level in the blood as a result of insulin deficiency, resistance or both. Globally, it has been deducted that the adult population with diabetes will rise by 69% for the year 2030. Thus, Bucholzia Coriacea (B. Coriacea) a perennial plant belonging to the family capparidaceae and genus Bucholzia is popularly known as wonderful kola. It’s also known as wonderful kola, its other name is called Garcinia kola .it has a long history of use in west Africa and central Africa, thus, the study on evaluation of potential in wonderful kola (buchiolizia coreica) seed extract on streptozotocin induced type 2 diabetes in male wister rats. Material and Methods: Fresh seeds of B. coriacea were plucked and washed with distilled water, the filtrate was concentrated using rotary evaporator and water bath. The extract was then weighed and stored in a refrigerator. 100g of crude extract and 1000mg of metformin was properly dissolved in 10ml of distilled water. The rats were carefully selected and separated into cages. 7 albino rats were used for normal control while 4 rats were kept in each of the remaining cages, and 6 replications were obtained, the test was carried out carefully by injecting the alloxan into the rats intraperitoneally and infecting them with diabetes mellitus, the following sets were made: normal group, negative and positive control group, while three groups were for extracts dosage. With exception of the normal control, all the groups were induced with diabetes. The extract (stem bark of Mangifera indica) will be administered orally to the three set of groups separately (i.e., one extract to one set). Determination of Fasting Blood Glucose Level by Intestinal Glucose Absorption. Results: Treatment groups receiving methanol Wonder Kola seed extract showed varying degrees of improvement in these parameters compared to the negative control group. Notably, Group VI, receiving the highest dose of the extract, demonstrated the most significant reduction in urea levels, suggesting a potential protective effect on renal function. The study investigated the effects of Wonder Kola seed extract on serum electrolytes, urea, and creatinine levels in alloxan-induced diabetic albino rats. Notably, significant variations were observed in these biochemical parameters across the different treatment groups. The study assessed the effects of methanol Wonder Kola seed extract on liver enzymes (AST, ALT, ALP) and serum protein levels (total protein, albumin, total bilirubin, direct bilirubin). Significant variations were observed in these parameters among the treatment groups compared to the normal and negative control groups. Treatment with the extract led to notable reductions in liver enzyme levels, indicating potential hepatoprotective effects. Conclusion: The findings of this study demonstrate the potential pharmacological benefits of methanol Wonder Kola seed extract in managing diabetes mellitus and associated complications.